INFLUENCE OF EDUCATION AND TRAINING, AND THE INVOLVEMENT OF USERS OF THE SYSTEM ACCOUNTING INFORMATION SYSTEM PERFORMANCE IN THE OFFICE SURABAYA MAIN BRANCH POST - Sari, Safira Mutiara; Ratnawati, Dyah (Yayasan Education and Social Center, 2023)
This research was conducted to determine the influencing factors of education and training programs, user involvement on the performance of the employee accounting information system at the Surabaya main branch post office. This research uses an explanatory method with a quantitative approach. The population used in this research were employees at the Surabaya main branch post office. The sample in this study was 48 people. The sampling technique used was purposive sampling. The data analysis technique in this research is multiple linear regression analysis, correlation coefficient, coefficient of determination, simultaneous test (F test) and partial test (t test). The results of this research show that education and training influence the performance of the accounting information system for employees of the Surabaya main branch post office. Meanwhile, user involvement among employees at the Surabaya main branch post office has no effect on the performance of the accounting information system for Surabaya main branch post office employees